External morphology of immature of Tynacantha marginata Dallas, 1851 (Hemiptera, Heteroptera, Pentatomidae) - Brugnera, Ricardo; Grazia, Jocélia (Zootaxa, 2018)
Immature stages of Neotropical Asopinae have been poorly studied. Here, the external morphology of eggs and nymphs of Tynacantha marginata Dallas are described using light and scanning electron microscopy. The egg is barrel-shaped with smooth surface, and long aero-micropylar processes. In the first instar, the color of abdomen varies along the development from yellow to red, the dorsal plates are pale, and the surface of evaporatorium bears spiked projections. From the second, the evaporatorium surface is reticulated. From third instar, the pronotum is orange with black lateral margins. The eggs and nymphs of T. marginata are unique among Neotropical Asopinae species of which the morphology is known, allowing the early identification of the species.